Breeding performance of the Blue Tit Parus caeruleus in a patchy Mediterranean landscape (REVUE D ECOLOGIE-LA TERRE ET LA VIE, 1999)
This study compares reproductive strategy and breeding success of Parus caeruleus in a helm-oak (Quercus rotundifolia) forest and a pine plantation (Pinus pinea and P. pinaster) in the southern Iberian Peninsula. During the breeding period, an asymmetric flow of individuals takes place from the helm-oak forest to the pine plantation. This flow is favoured by nestboxes where Blue tits can lay their eggs. During the winter, a large part of the population moves back from the pine plantation to the helm-oak forest. Breeding pair density was much higher in the helm-oak forest than in the pine plantation. This may bt accounted for by the poorer quality of the resources available in the pine plantation which birds try to compensate for with larger breeding territories. Breeding density and most life-history traits examined (timing of breeding, clutch site, egg size, number of fledglings and fledgling weight) were similar in both habitats, as a result of the phenotypic plasticity of this species. Although breeding success was similar in both habitats, recruitment of new individuals per unit area was higher in the helm-oak forest. The consequences of pine plantations, as a form of forestry management, on species conservation is discussed.
APS

Breeding patterns of the Great Tit (Parus major) in a pine plantation and a holm oak forest in a Mediterranean region (southern Spain) (Revue d'Ecologie la Terre et la Vie, 1996)
This study compares breeding patterns of nestbox-breeding Great Tits (Parus major) between two adjacent forest habitats: a pine plantation and a Mediterranean helm oak Quercus rotundifolia forest. Breeding density increased in both forests when nestbox density was raised. The breeding season started earlier in the pinewood, but tended to end at the same time in both habitats. Reproductive effort was higher in the plantation as reflected in egg volume rather than clutch size. Time of season had an effect on clutch size but not on the size of the eggs which remained constant throughout the breeding season. Breeding success was associated with habitat, with both the number of fledglings and their weight being higher in the pinewood. These parameters showed a seasonal trend in the pinewood but not in the helm oak forest. Our results show that Great Tit achieves a higher reproductive performance in the pinewood in spite of its recent settling in this habitat.
APS

Les peuplements de fourmis dans la Sierra Morena centrale (Espagne) rapports avec l'exposition et la vegetation (Insectes Sociaux, 1982)
Le but de ce travail est d'étudier l'influence d'un facteur biotique (la végétation) et d'un facteur abiotique (l'exposition) sur la distribution des especes de fourmis dans une zone de la Sierra Morena Centrale (Sud de l'Espagne). Pour cela, on a r6alis6 des 6chantil- lonnages stratifi6s dans chaque unit6 de v6g6tation, en soulane et en ombrée. L'analyse des correspondances a permis d'abord de s6parer les espèces trouvées dans les principaux types de v6gdtation de la zone d'étude (pâturage, reboisement de pins et zone inondée le long d'une rivière). Quand on supprime les relevés des endroits inondables, on peut distinguer les espèces indicatrices des zones oú prédominent soit le maquis ("matorral") soit le pâtturage ("dehesa"), ainsi que celles des zones exposées en soulane ou en ombrée. Dans la zone reboisée, il est impossible de distinguer des espèces indicatrices des associations végétales caractéristiques du milieu, ce qui peut s'interpréter comme une conséquence de l'homogénéisation due aux pratiques culturales.